A 3D transversally isotropic constitutive model for advanced composites implemented in a high performance computing code - Quintanas-Corominas, Adrià; Maimí, Pere; Casoni, Eva; Turon, Albert; Mayugo, Joan Andreu; Guillamet, Gerard; Vázquez, Mariano (European journal of mechanics, A, Solids, 2018)
A 3D constitutive damage model is proposed for predicting the progressive failure of laminated composite materials at mesoscopic length scale. The damage initiation and growth functions are based on the experimental phenomenology. The damage evolution laws are defined ensuring the energy regularization thanks to the crack band model. The crack closure effect under load reversal is also considered. The model is specifically formulated to be implemented in a high-performance computing platform, Alya, that enables the use of very fine meshes, ensuring an accurate prediction of the onset and propagation of damage. The reliability and the performance of the proposed formulation are examined simulating a cross-ply laminate and open hole tests under tensile loading. •The constitutive model is fully 3D transversally isotropic, formulated within the framework of continuum damage mechanics.•The model is suitable for a high performance simulation.•Failure process due to fibre kinking and breakage and matrix cracking are captured by the model.•New loading functions are proposed based on experimental observations and verified with a physically based failure criteria.•The damage laws are formulated as n-linear piecewise functions considering the crack-band model.